Smart Door System using Face Recognition Based on Raspberry Pi - Fadhillah Azmi; Insidini Fawwaz; Rina Anugrahwaty (Sean Institute, 2021)
A smart door system is a door with a smart digital lock system where someone can open the door or give permission to enter the house by authenticating the user. Basically, the technology used for smart door implementation uses a microcontroller as its controller and is combined with identification in the form of a password. The technology can be combined with other techniques, such as using facial recognition. This is done because data security using alphanumeric combination passwords is no longer used, so it is necessary to add security that is difficult to manipulate by certain people. The type of security offered is facial recognition biometric technology which has different characteristics. This study will design a smart door system that is built using Raspberry Pi-based facial recognition as a controller. The facial recognition algorithm will interact with the webcam and solenoid lock using the Raspberry Pi.Based on the results of the study, it was found that the smart door system with facial recognition can be done well and obtains an accuracy of 94%. The application of the smart door system proposed in this study is considered capable of increasing home security which can be controlled automatically using facial recognition. A smart door system is a door with a smart digital lock system where someone can open the door or give permission to enter the house by authenticating the user. Basically, the technology used for smart door implementation uses a microcontroller as its controller and is combined with identification in the form of a password. The technology can be combined with other techniques, such as using facial recognition. This is done because data security using alphanumeric combination passwords is no longer used, so it is necessary to add security that is difficult to manipulate by certain people. The type of security offered is facial recognition biometric technology which has different characteristics. This study will design a smart door system that is built using Raspberry Pi-based facial recognition as a controller. The facial recognition algorithm will interact with the webcam and solenoid lock using the Raspberry Pi.Based on the results of the study, it was found that the smart door system with facial recognition can be done well and obtains an accuracy of 94%. The application of the smart door system proposed in this study is considered capable of increasing home security which can be controlled automatically using facial recognition.